Blended learning strategy in teacher training programs - Byrka, Marian (My University, 2017)
The article examines the implementation of blended learning strategy in teacher training programs as an innovation in online learning. The blended learning idea comes from blending elements which use online technology with more traditional face-to-face teaching in the same course. The article analyses teacher training programs offered by Chernivtsi Regional Institute of Postgraduate Pedagogical Education. Additional data were gathered through a questionnaire administered to teachers who attended training courses. The characteristics of blended learning strategy, its benefits and limitations for teacher training are supported by a review of literature. The article closes with the comparison of curriculum components (content delivery, learner activities, materials, and required competences) between traditional and blended learning teacher training programs. Having obvious benefits in teacher training programs, the implementation of blended learning strategy sets some additional requirements to a learner, as well as to course instructors and lectors.
Keywords: ICT in learning, online leaning, blended learning, teacher training, curriculum